2020
DOI: 10.1002/dac.4346
|View full text |Cite
|
Sign up to set email alerts
|

Two‐sided matching framework for optimal user association in 5G multi‐RAT UDNs

Abstract: Summary Recently, academic and industrial research communities are paying more explicit attention to the 5G multiple radio access technology ultra‐dense networks (5G multi‐RAT UDNs) for boosting network capacity, especially in UD urban zones. To this aim, in this paper, we intend to tackle the user association problem in 5G multi‐RAT UDNs. By considering the decoupled uplink/downlink access (DUDA), we divide our user association problem into two distinct subproblems representing, respectively, the uplink and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…In contrast, a number of recent research papers relating to user association have incorporated matching theory as a result of its relatively low level of complexity [31][32][33][34][35]. In [31], the authors presented two frameworks that use auction games and matching theory to facilitate the efficient admission of secondary users into the HetNet.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a number of recent research papers relating to user association have incorporated matching theory as a result of its relatively low level of complexity [31][32][33][34][35]. In [31], the authors presented two frameworks that use auction games and matching theory to facilitate the efficient admission of secondary users into the HetNet.…”
Section: Related Workmentioning
confidence: 99%
“…The study presented in [32] investigated a matching game for user association and identified a solution that is close to optimal. In [33], the authors presented a pair of many-to-one matching games aimed to achieve optimal association for users in both downlink and uplink scenarios. In [34], the authors propose algorithms for resource allocation in 5G HetNets that are based on stable matching and support many-to-many relationships.…”
Section: Related Workmentioning
confidence: 99%
“…While authors in [12] used a Boston school mechanism for the uplink user association problem in HetNets. Two many-to-one matching games were proposed in [13] for optimal user association in the uplink and downlink in 5G multiple radio access technology ultra-dense networks. The work in [14] considered the problem of joint user association and channel assignment with proportional fairness signal-to-interference-plus-noise ratio (SINR) based power allocation in downlink multi-cell non-orthogonal multiple access (NOMA) networks.…”
Section: A Related Workmentioning
confidence: 99%
“…Resource allocation [30], [31], [32], [33] is considered a key problem to resolve in 5G-IoT networks, especially for network slicing architecture [34]. The latter needs to share independently different resources with several slices offering various services in order to meet the device's QoS requirements.…”
Section: Related Workmentioning
confidence: 99%